Determination of Iron (Fe) Species in Samples of Canned Packaging Beef - Haryanti, Septi Dwi; Dzawinnuha, Hannuna; Adika, Vanadia (Indonesian Journal of Chemistry and Environment, 2017)
The research aims to know the content of iron metal (Fe) in samples of canned packaging beef. The destruction of the samples prior to breaking the metallic bond with organic compounds in the sample, making them easier to identify the metal content to be analyzed. The analysis of metal content of iron has been done by using Atomic Absorption Specthrophotometer. The level of iron metal contained in beef samples of A brand packaging is 40.0570 mg/kg, in B brand packaging is 25.5175 mg / Kg and in the Â C brand packaging 22.9600 mg/Kg. When compared to the iron metal threshold in food as contained in SNI 01-7387-2009, then the sample of beef packaging for B and C brand is still safe because the iron content is still below 30 mg/kg. Meanwhile,Â  the beef corned for A brand is not safe because it is higher than 30 mg/kg.